2013
DOI: 10.4103/0974-1208.126308
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive parameters and oxidative stress status of male rats fed with low and high salt diet

Abstract: BACKGROUND:Deficiency of minerals and micronutrients has been reported to impair the process of spermatogenesis. Historically, salt has been used by women on their husbands to increase their libido, however, the role of salt diet on sperm parameters are yet to be ascertained.AIM:The present study was designed to determine the effect of low and high salt diet on sperm parameters, oxidative status and reproductive hormone levels of male rats.MATERIALS AND METHODS:A total of 18 rats were divided into three groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…Similar to previous studies, Iranloye et al [37] indicated that rats that received NaCl at 8% exhibited a relatively high MDA level in the epididymis compared to the controls. The activities of SOD, GSH, and CAT enzymes in testicular and epididymal tissues were significantly reduced by increased dietary salt in rats [37]. The high levels of MDA and SOD in the testis of rats fed a high salt diet can be attributed to free radical harm, confirming the harmful influences of the high salt intake on the reproductive patterns.…”
Section: Antioxidant Indicessupporting
confidence: 86%
See 3 more Smart Citations
“…Similar to previous studies, Iranloye et al [37] indicated that rats that received NaCl at 8% exhibited a relatively high MDA level in the epididymis compared to the controls. The activities of SOD, GSH, and CAT enzymes in testicular and epididymal tissues were significantly reduced by increased dietary salt in rats [37]. The high levels of MDA and SOD in the testis of rats fed a high salt diet can be attributed to free radical harm, confirming the harmful influences of the high salt intake on the reproductive patterns.…”
Section: Antioxidant Indicessupporting
confidence: 86%
“…GSH and catalase activities did not significantly differ between the high salt and control groups [24]. Similar to previous studies, Iranloye et al [37] indicated that rats that received NaCl at 8% exhibited a relatively high MDA level in the epididymis compared to the controls. The activities of SOD, GSH, and CAT enzymes in testicular and epididymal tissues were significantly reduced by increased dietary salt in rats [37].…”
Section: Antioxidant Indicessupporting
confidence: 81%
See 2 more Smart Citations
“…Fang, Zhong, Sun, and Zhou (2018) reported similar effects including decreased reproductive performance and mRNA expression of heat shock protein 70, the receptor tyrosine kinase and cyclin A which are key genes for spermatogenesis. HSD has also been reported to decrease luteinising hormone (LH) level and increase epididymal oxidative stress and abnormal sperm cells (Iranloye, Oludare, Morakinyo, Esume, & Ekeh, 2013). One mechanism by which HSD induces hypertension is by generation of reactive oxygen species which when generated in excess of the endogenous antioxidants causes oxidative stress (Dobrian, Schriver, Lynch, & Prewitt, 2003).…”
Section: Introductionmentioning
confidence: 99%